Pengaruh Pemberian Nugget Modifikasi Hati Ayam Boiler dan Daun Bayam Hijau terhadap Peningkatan Kadar Hemoglobin Remaja Putri di MAN Rejang Lebong - Aprilia, Maya; Sadiq, Ahmad; Nazarena, Yunita; Sari, Winda (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2025)
ABSTRACT Background: Iron nutritional anemia is the biggest micronutrient problem in Indonesia, which occurs in groups of toddlers, school children, pregnant women, women and adult men. In general, anemia is a condition where the hemoglobin level is lower than normal. According to WHO, in 2021, the prevalence of anemia in productive women (15-54) in the world is around 29.9%. Objective: This research aims to determine the effect of giving modified boiler chicken liver nuggets and green spinach leaves on increasing hemoglobin levels in anemic adolescent girls. This research was conducted from 22 April to 06 May 2024 at MAN Rejang Lebong Research Method: used in this research was the Quasy Experiment method with a one group pre-post test design, namely a quasi-experiment carried out on one group. The sample was selected using quota sampling with a sample size of 41 people. Results: statistical tests showed that the effect of giving modified chicken liver nuggets and green spinach leaves showed that the average Hemoglobin level before the intervention was 10.89 g/dL with a standard deviation of 1,037 and after the intervention it was 11.55 g/dL with a standard deviation of 1,470 Results The difference in the average measurement of hemoglobin levels before and after was 0.73 g/dL with a standard deviation of 1.253. The statistical test results obtained a p value = 0.000, so it can be concluded that there was an effect of giving modified chicken liver nuggets and green spinach leaves on increasing Hemoglobin levels before and after the intervention. Conclusion: There is an effect of giving modified boiler chicken liver nuggets and green spinach leaves on increasing hemoglobin levels in adolescent girls Keywords: Nugget, Anemia, Boiler Chicken Liver, Green Spinach